Исследование свободнорадикальных процессов при микотоксикозе, вызванном введением охратоксина и при лечении - Л. М. Овсепян; А. А. Аракелян; М. Г. Малакян; Г. С. Казарян; А. В. Зангинян (ՀՀ ԳԱԱ հրատ.)
Целью исследования было изучение процесса перекисного окисления липидов при микотоксикозе в печени и плазме крови прoизводными оснований Шиффа аминокислот (пиколинил-L-фенилаланина, пиколинил-L-триптофана и никотинил-L-триптофан) в дозе 5 и10 мг/кг. Микотоксикоз вызывали пероральным введением охратоксина в течение 21дня в дозе 25 мг/кг. Как показали результаты исследования, введение охратоксина сопровождается увеличением содержания малонового диальдегида – одного из продуктов перекисного окисления липидов. Հետազոտության նպատակն էր կենդանիների մոտ ուսումնասիրել օխրատոքսինով առաջացվող միկոտոքսիկոզի և ամինաթթուների շիֆային հիմքերի ածանցյալների (պիկոլինիլ-L-ֆենիլալանին, պիկոլինիլ-L-տրիպտոֆան և նիկոտինիլ-L-տրիպտոֆան) 5 և 10 մգ/կգ չափաբաժնով բուժման ժամանակ ազատ ռադիկալային գործընթացները:The aim of the study was to investigate the process of lipid peroxidation during mycotoxicosis in liver and blood plazma and the treatment bases amino acid Schiff (picolinyl-L-phenylalanine, picoline-L-tryptophan, and nicotine-L-tryptophan) at a dose of 5 and 10 mg / kg. Mycotoxicosis caused by oral administration of ochratoxin during 21day at a dose of 25 mg / kg. The results of the study showed that the introduction of ochratoxin leaded the increase in the content of malondialdehyde – one of the products of lipid peroxidation. Introduction of drugs leads to the normalization process of lipid peroxidation
Keywords: Biology; Molecular Biology